EU Citizens in the European Public Sphere : An Analysis of EU News in 27 EU Member States - Walter, Stefanie (Studies in International, Transnational and Global Communications, 2017)
Stefanie Walter examines the visibility of European Union citizens in the mass mediated European public sphere and argues that it can help facilitate an exchange between decision-makers and ordinary citizens. The results show that in comparison to other actor groups, such as political parties or civil society organisations, the visibility of European Union citizens is not marginal. Yet, the image of the European Union citizenry that becomes visible via the news media remains nationally entrenched and references to a truly European citizenry are rare. The study also uses multilevel regressions to explain the visibility of European Union citizens in the news coverage. The empirical analyses are based on a large-scale content analysis of TV news and newspaper articles of the 2009 European Parliament election. Content Citizenship, Democracy, European Union Normative Public Sphere Theories European Public Sphere Visibility of EU Citizens in the European Public Sphere Target Groups Students and lecturers in European and comparative politics, political and transnational communication Decision makers in European Union affairs The Author Stefanie Walter is a post-doctoral researcher at the Chair of Communication Studies, Climate and Science Communication at the University of Hamburg. Her research interests are in political and transnational communication, as well as European politics. .